Удосконалення організації вагонопотоків в сучасних умовах - Сіконенко, Григорій Михайлович; Мухортова, Кристина Андріївна (НТУ "ХПІ", 2015)
Розглядається організація вагонопотоків з урахуванням наявності вагонів інших держав та компаній операторів. Підвищення дальності прямування поїздів істотно впливає на термін доставки вантажу за рахунок ліквідації переробки на попутних технічних станціях, що особливо важливо відносно вагонів що не належать Укрзалізниці, оскільки плата за їх використання значно вища. Пропонується збільшити транзитність вагонопотоку за рахунок формування неповновагових поїздів із поповненням до повної маси на шляху прямування за умови економічної доцільності згідно із наведеною моделлю. Результати досліджень можуть бути використані при розробці мережевого плану формування поїздів.

In the article the problems connected with the car traffic volume organization are considered. Based on the analysis of existing methods of the car traffic volume organization it is found that much of the parameters in the calculation of plan formation schedule is not included in full. An amount of the cars belonging to other states, companies and operators is more than one third, and there are certain restrictions are in the conditions of use, so it will be improve the current system takes into account the car traffic volume priority. Increase range of movement of trains significantly affect the delivery time by eliminating the processing free technical stations that most importantly regarding cars not belonging to Ukrainian Railways as payment for their use is much higher. In this paper, it is proposed the technique of increasing economic evaluation of car traffic volume transit by forming of trains with incomplete amount of the cars with completion to full amount during transition. The research results can be used and integrated into an automated system of train formation network plan development.
Improvement of the organization of traffic volumes in modern conditions
Keywords: залізничний транспорт; план формування поїздів; рівень транзитності; операторські компанії; car traffic volume; train formation plan; transit level; own car